Recent Advances of a Box Model to Represent the Estuarine Dynamics: Time‐Variable Estuary Length and Eddy Diffusivity. (9th April 2021) - Verri, Giorgia; Mahmoudi Kurdistani, Sahameddin; Coppini, Giovanni; Valentini, Andrea
Abstract: This study starts from a two‐layer 1D Estuary Box Model (EBM), the so called Centro Euro‐Mediterraneo sui Cambiamenti Climatici (CMCC) EBM (Verri et al., 2020, https://doi.org/10.1016/j.ocemod.2020.101587 ), devised to offer a proper representation of the net river release in a coupled modeling framework with hydrology models and ocean models reaching the mesoscale. Two key advances are proposed in the present study: (I) the estuary length and (II) the horizontal eddy diffusivity coefficient are no longer considered as static parameters to calibrate but two non‐dimensional equations have been introduced in order to make them time‐variable. The Goro branch of the Po river delta is considered as case study of "salt‐wedge estuary" flowing into a microtidal sea. Regarding the estuary length, a non‐dimensional equation has been tested and validated. This equation provides a time dependent estuary box volume which is more realistic choice. This time‐variable estuary length represents the length of the salt wedge intrusion. Regarding the horizontal eddy diffusivity, the static eddy coefficient adopted in the previous version of the model is a coarse assumption. Thus a non‐dimensional equation for this coefficient has been tested and validated. It makes the eddy diffusivity dependent on the velocity shear, the salinity gradient and the estuary geometry. The proposed dynamic formula is found to enhance the model capability to reproduce the salinity at the estuary mouth. Overall the high statistical performance in terms of RMSE and correlation coefficient, the short CPU time and the minimal calibration encourage to use the CMCC EBM in coupled mode with both mesoscale‐resolving ocean and hydrology models to produce operational forecasts and climate scenarios. Plain Language Summary: The Centro Euro‐Mediterraneo sui Cambiamenti Climatici Estuary Box Model is placed in the framework of developing a conceptual and numerical modeling approach to simulate the effects of river release on the coastal to open sea circulation and dynamics. The few kilometers resolution of mesoscale ocean models cannot explicitly resolve the estuary dynamics; thus, the idea of an "estuary box model" that gives reasonable values of water volume flux and salinity at the river mouth, which in turn affects the ocean dynamics. A further development of the model equations is offered in this article and is demonstrated to enhance the model capability to reproduce the salinity at the estuary mouth; moreover, the length of the salt wedge intrusion is considered a model unknown. The research is not only interesting from an academic point of view but also for its practical application: (i) introducing an information on river release into ocean models, from regional to global scale, can improve their performance and produce more realistic operational forecasts or climate scenarios; (ii) introducing an estimate of the length of the salt wedge contributes to address the pressing issue of salt water intrusion and salinization processes in coastal areas. Key Points: An Estuary Box Model is devised to represent the salt‐wedge intrusion length and the net river release at the estuary mouth Two key advancements, that is non‐dimensional equations for time‐variable estuary length and eddy diffusivity, enhance the model performance The proposed model is suitable for coupling with mesoscale ocean and hydrology models to produce operational forecasts and climate scenarios